Ensuring the State’s Legal Liability is the Key Challenge of Legal Reform in the Modern Ukraine - O. S. Bakumov (Bulletin of Kharkiv National University of Internal Affairs)
Special attention has been paid to the fact that the doctrine of legal liability of the state to a person is increasingly affirmed in Ukraine as a theoretical basis for the functioning of state power in general and all its agencies in particular. However, despite the large number of scientific developments, the national legal science still can not boast of an unambiguous and generally recognized understanding of the essence of the phenomenon of legal liability of the state.